1999
DOI: 10.1038/sj.bjp.0702597
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional effects of the neuroactive steroid tetrahydrodeoxycorticosterone on GABA‐activated Cl currents in cultured rat hypothalamic neurons

Abstract: 1 The non-genomic e ects of tetrahydrodeoxycorticosterone (THDOC; were studied in cultured hypothalamic neurons of the rat.2 The e ects of THDOC (10 nM ± 1 mM) on responses to di erent concentrations of exogenously applied GABA and on spontaneous inhibitory postsynaptic currents (IPSCs) were measured with whole-cell voltage clamp recordings. 3 Application of GABA induced inward currents with dose-dependently increasing amplitudes (up to 3.9 nA at a holding potential of 720 mV). High doses of THDOC (100 nM ± 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 38 publications
0
15
4
Order By: Relevance
“…In the present study, the effect of THDOC on sIPSC was different from other neuronal types. High concentration of THDOC increased decay time of sIPSC but had no effect on the amplitude in many cell types (Cooper et al, 1999;Wetzel et al, 1999). However, both amplitude and decay time of sIPSC were increased in the present study.…”
Section: Regional and Cell-type Dependent Differences In Gaba A R Modcontrasting
confidence: 76%
“…In the present study, the effect of THDOC on sIPSC was different from other neuronal types. High concentration of THDOC increased decay time of sIPSC but had no effect on the amplitude in many cell types (Cooper et al, 1999;Wetzel et al, 1999). However, both amplitude and decay time of sIPSC were increased in the present study.…”
Section: Regional and Cell-type Dependent Differences In Gaba A R Modcontrasting
confidence: 76%
“…Recent studies have indicated the existence of at least three neurosteroid binding sites on the GABA-A receptor: one for allosteric enhancement of GABA-evoked currents by allopregnanolone, one for direct activation by allopregnanolone, and one for antagonist action of sulfated neurosteroids such as PS (Lambert et al, 2003; Hosie et al, 2007). Electrophysiological studies are extensively used to confirm that neurosteroids, at low (nM) concentrations, act as positive allosteric modulators of GABA-A receptor function (Harrison et al, 1987; Kokate et al, 1994; Wetzel et al, 1999). Hence, neurosteroids enhance the specific receptor binding of [ 3 H]flunitrazepam, a benzodiazepine receptor agonist, and [ 3 H]muscimol, a specific GABA-site agonist, and inhibit the binding of [ 35 S] t -butylbicycloorthobenzoate (TBPS), a cage convulsant and noncompetitive GABA-A receptor antagonist.…”
Section: Mechanisms Of Neurosteroid Actionsmentioning
confidence: 99%
“…When THDOC was added to the bath flow solution at a concentration of 1 μ M , the amplitude of these GABA A currents was increased in a reversible manner by about 50% (Figure 2b, c). Wetzel et al (1999) observed that at low concentrations, THDOC had an inhibitory action. We therefore repeated these experiments at concentrations as low as 10 n M (Figure 2b, d), but failed to detect any inhibition by THDOC at these concentrations.…”
Section: Resultsmentioning
confidence: 98%
“…In either case, it is now well established that neurosteroid actions are often dependent on the subunit composition of the GABA A receptor (Maitra and Reynolds, 1999; Bianchi and Macdonald, 2001). The neuroactive steroid THDOC itself is remarkable, because it has been observed, that in some preparations, THDOC turns from an inhibitor of GABA currents to an activator as concentration increases (Wetzel et al , 1999). Thus, THDOC could potentially have no effect, an inhibitory or an excitatory activity on any specific population of neurones, depending on nature of the particular GABA A receptors and the local concentration of steroid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation